Comparative Study of Risk Profiles for Non-Communicable Diseases in Urban and Suburb Adolescents in Padang City (Indonesia) - Neherta, Meri; Nurdin, Yonrizal (Open Access Macedonian Journal of Medical Sciences, 2021)
Adolescence is when we still like to experiment and often develop bad habits which may lead to non-communicable diseases (NCDs) in the future. This study aimed to understand the lifestyle at risk of non-communicable diseases in adolescents that live in the urban and rural areas of Padang city. This research method is comparative descriptive with a descriptive-analytical approach, with a total sample of 788 people. The study was conducted from March 2019 to November 2019. Results: A total of 57.77% of respondents in urban areas and 69.54% of respondents in rural areas like to eat junk food. 45.35% urban respondents and 60.21% rural respondents like to consume high-sweetened beverages. 73.4% of urban respondents and 7.6% of rural respondents like to smoke. 80.6% of urban respondents and 87.8% of rural respondents lack physical activity. 59.9% of urban respondents and 49.05% of rural respondents do not like to exercise. 67% of urban respondents and 80.2% of rural respondents sleep late at night. Conclusion: The risk behavior of non-communicable diseases in rural adolescents is higher than in urban adolescents. It is recommended that parents, teachers, and health workers work together to carry out intervention activities for healthy lifestyles for all adolescents.